Alternaria alternata infection in tomato adversely affects the nutritional parameters of tomato - Tiwari, A.; Upadhyay, R. S. (International Journal of Agricultural Technology, 2016)
The study aims the determination of nutritional components in tomato fruits after infection by Alternaria alternata. The tomato (Solanum lycopersicum) a foremost vegetable crop, possesses significant number of nutritional components which provide prevention and cure for various important diseases. Tomato plants are sternly affected by the fungus A. alternata which causes stem canker, leaf spot, and fruit rot diseases. The objective of the present study was to investigate the lycopene, β-carotene, total carotenoides and proline content in tomato fruits infected by A. alternata. The lycopene content was observed maximum at 0-hours after treatment with A. alternata and was found to be declined up to 96-hours. The highest percent decrease in lycopene content of 85.12% was calculated in 96 hours after treatment. A similar trend was also observed in the case of β-carotene and total carotenoids content. The highest decrease of 30.82% in β-carotene and 73.92% in total carotenoides was observed in 96 hours after treatment with A. alternata. An increment in proline content was found in every 24 hours and the maximum content was estimated at 96-hours after treatment of A. alternata. The results indicated that A. alternata has a colossal effect on all the studied components of tomato fruits.